Technologies for supporting reasoning communities and collaborative decision making cooperative approaches - Yearwood, John 1954-; Stranieri, Andrew (Information Science Reference, 2011)
"This book covers diverse fields of enquiry including decision science, political science, argumentation, knowledge management, cognitive psychology and business intelligence, giving a perspective on group reasoning that ultimately aims to lead to a greater understanding of reasoning communities and informed technological developments"--Provided by publisher